Cerebrospinal fluid biomarkers and clinical features in leucine‐rich repeat kinase 2 (LRRK2) mutation carriers. Issue 6 (4th April 2016) - Vilas, Dolores; Shaw, Leslie M.; Taylor, Peggy; Berg, Daniela; Brockmann, Kathrin; Aasly, Jan; Marras, Connie; Pont‐Sunyer, Claustre; Ríos, José; Marek, Ken; Tolosa, Eduardo
ABSTRACT: Background: Mutations in the leucine‐rich repeat kinase 2 ( LRRK2 ) gene are the most common cause of inherited Parkinson's disease (PD). Nonmanifesting carriers of LRRK2 mutations are at high risk for developing PD. Information available on cerebrospinal fluid (CSF) biomarkers in LRRK2 carriers remains preliminary. Objectives: To measure CSF levels of α‐synuclein, β amyloid1‐42, total‐tau, and phospho‐tau181, in LRRK2‐ associated PD, idiopathic PD, nonmanifesting carriers, and first‐degree relatives of LRRK2‐ associated PD patients without the mutation (nonmanifesting noncarriers). To correlate the clinical features and the integrity of the nigrostriatal pathway assessed by neuroimaging with the CSF biomarkers. Methods: 138 CSF samples provided by the Michael J. Fox Foundation LRRK2 Cohort Consortium were analyzed: 28 LRRK2‐ associated PD, 35 idiopathic PD, 41 nonmanifesting carriers, and 34 nonmanifesting noncarriers. All of the participants in the study were clinically assessed. Most of the participants underwent a dopamine transporter scan to assess the integrity of the nigrostriatal pathway. Results: CSF levels of α‐synuclein were similar in LRRK2‐ associated PD, nonmanifesting carriers, and nonmanifesting noncarriers but significantly higher than in idiopathic PD ( P  = .041). No differences were found in the concentrations of β amyloid1‐42, total‐tau, or phospho‐tau181 among study groups. CSF alpha‐synuclein levels strongly correlated with total‐tau and phospo‐tau181 levels in all groups. No significant correlation was found between the CSF biomarkers and the striatal binding ratios for (123)I‐FP‐CIT in nonmanifesting carriers. Conclusion: The CSF protein profile differs in LRRK2‐ associated PD and idiopathic PD, suggesting that pathophysiological mechanisms different from IPD underlie LRRK2‐ associated PD. Cerebrospinal fluid biomarkers did not prove helpful in differentiating asymptomatic LRRK2 mutation carriers from noncarriers. © 2016 International Parkinson and Movement Disorder Society